A high red hardness alloy material and preparation method thereof
By using laser cladding method to cladding N-tungsten carbide tantalum micropowder on the surface of M2 high-speed steel substrate, the problem of insufficient red hardness in traditional alloy materials under high temperature conditions is solved, and a low-cost and high-efficiency high-red hard alloy is achieved Material production.
Patent Information
- Application Number
- CN202411514355.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Traditional alloy materials have insufficient red hardness under high temperature conditions and are relatively high in cost. The traditional doping effect is approaching the limit, making it difficult to further improve red hardness.
Laser cladding method is used to cladd the surface of the M2 high-speed steel matrix to cladd the materials such as N-tungsten carbide tantalum, chromium carbide powder and nickel powder to form high-red hard alloy materials with excellent red hardness and low cost.
It realizes low-cost production of high-red hard alloy materials, the process is compatible with laser cladding technology, simple process operation and high production efficiency, the red hardness of the cladding layer is comparable to that of M42 high-speed steel, and has better thermal fatigue resistance and stability.
Smart Images

Figure CN119040720B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloy materials, and in particular, relates to a high red hardness alloy material and a preparation method thereof. Background Art
[0002] The red hardness of an alloy refers to the ability of a material to maintain hardness under high temperature conditions. It is an important performance indicator for evaluating high-temperature materials such as high-speed cutting tools and hot working die steel. Specifically, red hardness describes the material's ability to resist softening at high temperatures.
[0003] The improvement of red hardness of traditional alloy materials depends on adding a large amount of expensive alloy elements, such as Co, Mo, W, V, etc. For example, the traditional M2 high-speed steel is doped with Co element, and the obtained M35, M42 and other alloy materials have good red hardness, but the cost of alloy materials is relatively high, and the traditional doping effect has reached its limit.
[0004] With the development of laser technology, high red hardness materials are clad on the surface of traditional base alloy materials through laser cladding process, which not only gives the alloy material good surface red hardness, but also maintains good strength and toughness of the core material. Among them, tungsten carbide has excellent red hardness. Using it as the base material for cladding can effectively improve the surface red hardness to a certain extent. However, the traditional tungsten carbide has a large particle size and is brittle. It lacks strength and toughness after cladding forming, and is prone to fatigue cracks during the service of the product, which seriously restricts the development of cladding-type high red hardness alloy materials. Summary of the invention
[0005] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a high red hardness alloy material and a preparation method thereof.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A high red hardness alloy material consists of an M2 high-speed steel substrate and a cladding layer, wherein the cladding material of the cladding layer is composed of the following components: 52-58wt% N-tungsten carbide tantalum powder, 6.5-9wt% chromium carbide powder and 3.2-4.4wt% nickel powder, and the balance is atomized iron powder.
[0008] The N-tungsten carbide tantalum powder is prepared by the following method:
[0009] Step A1: Diethylenetriamine, sodium hydroxide and anhydrous acetone are mixed, dry nitrogen is introduced for protection, the temperature is controlled at 0-10°C in an ice-water bath, stirring is applied at 180-240 rpm, cyanuric chloride is slowly added to react for 1.5-2h, then the temperature is raised to 45-55°C and the reaction is continued for 2-3h. After the reaction is completed, the mixture is filtered and rotary evaporated to obtain a template;
[0010] Furthermore, the dosage ratio of cyanuric chloride, diethylenetriamine, sodium hydroxide and anhydrous acetone is 0.1 mol: 0.16-0.17 mol: 0.5-0.7 g: 85-100 mL, and sodium hydroxide is used as an alkaline absorbent to promote the substitution of the active amine group of diethylenetriamine with cyanuric chloride to form nitrogen-carbon-rich compound clusters.
[0011] Step A2: premix the template and dimethylacetamide aqueous solution, then add tungsten hexachloride and tantalum ethoxide and mix well, increase the pressure to 2.5-3.5 bar, raise the temperature to 100-115°C, slowly inject ammonia water, reflux for 4-5 hours, centrifuge after the reaction, take the bottom precipitate, wash and dry to obtain a precursor;
[0012] Furthermore, the dosage ratio of tungsten hexachloride, tantalum ethoxide, template, ammonia water and dimethylacetamide aqueous solution is 1g: 0.14-0.18g: 0.8-1g: 5-8mL: 30-40mL, and the poly-nitrogen structure of the template forms a complex to capture tungsten and tantalum in a liquid environment, and forms a complex after hydrolysis.
[0013] Step A3: placing the precursor in a plasma sintering furnace, performing carbonization roasting and nitridation sintering in sequence, and then cooling the precursor to 500° C. and air cooling the precursor out of the furnace, and grinding and dispersing the precursor to obtain N-tungsten carbide tantalum powder;
[0014] Furthermore, the temperature of carbonization calcination is 550-620° C., and the calcination time is 1.2-1.6 h.
[0015] Furthermore, the temperature of the nitriding sintering is 1450-1520° C., and the sintering time is 15-20 min.
[0016] A method for preparing a high red hardness alloy material comprises the following steps:
[0017] Step S1: grinding the surface of the M2 high-speed steel substrate, cleaning the ground surface with ethanol, and drying to obtain a component to be coated;
[0018] Step S2: Mix the raw materials of the cladding material and spread them on the surface of the part to be clad, perform laser cladding under the protection of argon gas, and machine the cladding surface after cooling to obtain a high red hardness alloy material.
[0019] Furthermore, the spreading thickness of the cladding material is 0.25-0.3 mm.
[0020] Furthermore, the laser power of the laser cladding is 1.5-1.7 kW, and the laser scanning rate is 250-300 mm / min.
[0021] Beneficial effects of the present invention:
[0022] The present invention adopts the laser cladding method to give the alloy material excellent red hardness. Compared with traditional high red hardness alloys such as M35 and M42, the amount of precious metal doping is lower, which greatly reduces the cost of the product. In addition, the process of the alloy material is compatible with the laser cladding technology, the process operation is simple, and the production efficiency is high.
[0023] The invention discloses a cladding material formula compatible with laser surface treatment technology, wherein independently developed N-tungsten carbide tantalum micropowder is introduced into traditional cladding raw materials, wherein diethylenetriamine and cyanuric chloride are substituted to prepare nitrogen-carbon-rich compound clusters, namely, template agents, and the complexation of the multi-component nitrogen structure in the template agent structure is utilized to capture tungsten and tantalum elements in a liquid environment, and high-temperature hydrolysis is performed to form a composite, namely, a precursor, and during the calcination process in a plasma sintering furnace, the template agent is thermally decomposed to form a composite carbide with tungsten and tantalum, and the decomposed nitride is in-situ nitrided and doped with the composite carbide at high temperature to form nitrogen-doped tungsten carbide tantalum microparticles, which themselves have excellent heat resistance and high-temperature hardness, and the cladding layer formed by the compounding thereof has excellent red hardness. Compared with the traditional nitriding strengthening process, the N-tungsten carbide tantalum micropowder introduced by the invention is The efficiency of nitrogen doping is high and the nitriding layer is uniform, the performance of each particle is uniform, it is not easy to form internal stress in the cladding layer, which is conducive to the formation of a stable cladding layer; secondly, along with the thermal decomposition of the template, the complex tungsten-tantalum cluster structure disintegrates, which is conducive to the formation of dense particles. Combined with the scanning electron microscope, it can be seen that the N-tungsten carbide tantalum powder is a particle with a submicron structure, which is easier to form a dense cladding layer during the laser cladding process, greatly reducing internal defects, thereby improving the red hardness of the cladding layer; in addition, the particles with a submicron structure themselves form solid solution strengthening in the cladding layer, and at the same time promote the grain refinement of the cladding layer, thereby improving the red hardness of the cladding layer; the hardness of the alloy material prepared by the present invention after treatment at 600°C is maintained at 63.9-65.1HRC, showing excellent red hardness. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0025] Figure 1 This is a scanning electron microscope image of N-tungsten carbide tantalum powder prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1, preparation of high red hardness alloy material, the specific implementation process is as follows:
[0028] (1) Preparation of N-tungsten carbide tantalum powder
[0029] Step A1: Take diethylenetriamine, sodium hydroxide and anhydrous acetone and mix them, introduce dry nitrogen for protection, control the temperature at 10°C in an ice-water bath, apply stirring at 240rpm, slowly add cyanuric chloride to react for 1.5h, then raise the temperature to 55°C and continue the reaction for 2h, wherein the amount ratio of cyanuric chloride, diethylenetriamine, sodium hydroxide and anhydrous acetone is 0.1mol:0.17mol:0.7g:100mL. After the reaction is completed, filter to remove sodium hydroxide, and remove acetone by rotary evaporation to obtain a template.
[0030] Step A2: pre-mix the template and dimethylacetamide aqueous solution, then add tungsten hexachloride and tantalum ethoxide and mix well, increase the pressure to 3.5 bar, raise the temperature to 115°C, slowly inject ammonia water, and reflux for 4 hours, wherein the dosage ratio of tungsten hexachloride, tantalum ethoxide, template, ammonia water and dimethylacetamide aqueous solution is 1g:0.14g:1g:8mL:40mL, the volume fraction of dimethylacetamide aqueous solution is 60%, and the ammonia water adopts an industrial raw material with a mass fraction of 20%. After the reaction is completed, centrifuge to take the bottom precipitate, wash and dry to obtain a precursor.
[0031] Step A3: Place the precursor in a plasma sintering furnace, first perform carbonization roasting at 620°C for 1.2 hours, then continue to heat up to 1520°C for nitridation sintering for 15 minutes, cool to 500°C, take out of the furnace and air cool, grind and disperse, and obtain N-tungsten carbide tantalum powder.
[0032] (2) Preparation of high red hardness alloy materials
[0033] Preparation of cladding material: take raw materials according to weight percentage, 52wt% of N-tungsten carbide tantalum micropowder, which is self-made in this embodiment; 9wt% of chromium carbide powder, which is selected from FCr3C2-1 type raw material of Zhuzhou Guangyuan Hard Materials Co., Ltd.; 4.4wt% of nickel powder, which is selected from MDNi-A1 type raw material of Jiangsu Mengda New Materials Technology Co., Ltd.; 34.6wt% of atomized iron powder, which is selected from HT40.37 type raw material of Hangzhou Yitong New Materials Co., Ltd.
[0034] Step S1: Take the cut M2 high-speed steel substrate, polish the surface with 150-grit sandpaper, and then clean and dry the polished surface with ethanol to obtain a component to be covered.
[0035] Step S2: Add the raw materials of the cladding material into a high-speed mixer and mix them at a high speed of 1000 rpm for 10 minutes. Then, spread them evenly on the surface of the part to be clad through a distributor. The spreading thickness of the cladding material is controlled to be 0.3 mm. Laser cladding is performed under argon protection. The laser power of the laser cladding is 1.7 kW and the laser scanning rate is 250 mm / min. After cladding, the material is air-cooled to room temperature. The cladding surface is machined to achieve the designed size to obtain a high red hardness alloy material.
[0036] Example 2, preparation of high red hardness alloy material, the specific implementation process is as follows:
[0037] (1) Preparation of N-tungsten carbide tantalum powder
[0038] Step A1: Take diethylenetriamine, sodium hydroxide and anhydrous acetone and mix them, pass dry nitrogen for protection, control the temperature at 0°C in an ice-water bath, apply stirring at 180rpm, slowly add cyanuric chloride to react for 2h, then raise the temperature to 45°C and continue the reaction for 3h, wherein the amount ratio of cyanuric chloride, diethylenetriamine, sodium hydroxide and anhydrous acetone is 0.1mol:0.16mol:0.5g:85mL. After the reaction is completed, filter to remove sodium hydroxide, and remove acetone by rotary evaporation to obtain a template.
[0039] Step A2: pre-mix the template agent and dimethylacetamide aqueous solution, then add tungsten hexachloride and tantalum ethoxide and mix well, increase the pressure to 2.5 bar, raise the temperature to 100°C, slowly inject ammonia water, and reflux for 5 hours, wherein the dosage ratio of tungsten hexachloride, tantalum ethoxide, template agent, ammonia water and dimethylacetamide aqueous solution is 1g:0.18g:0.8g:5mL:30mL, the volume fraction of dimethylacetamide aqueous solution is 60%, and the ammonia water adopts an industrial raw material with a mass fraction of 20%. After the reaction is completed, centrifuge to take the bottom precipitate, wash and dry to obtain a precursor.
[0040] Step A3: Place the precursor in a plasma sintering furnace, first perform carbonization roasting at 550°C for 1.6 hours, then continue to heat up to 1450°C for nitridation sintering for 20 minutes, cool to 500°C, take out of the furnace and air cool, grind and disperse, and obtain N-tungsten carbide tantalum powder.
[0041] (2) Preparation of high red hardness alloy materials
[0042] Preparation of cladding material: take raw materials according to weight percentage, 58wt% of N-tungsten carbide tantalum micropowder, which is self-made in this embodiment; 6.5wt% of chromium carbide powder, which is selected from FCr3C2-1 type raw material of Zhuzhou Guangyuan Hard Materials Co., Ltd.; 3.2wt% of nickel powder, which is selected from MDNi-A1 type raw material of Jiangsu Mengda New Materials Technology Co., Ltd.; 32.3wt% of atomized iron powder, which is selected from HT40.37 type raw material of Hangzhou Yitong New Materials Co., Ltd.
[0043] Step S1: Take the cut M2 high-speed steel substrate, polish the surface with 150-grit sandpaper, and then clean and dry the polished surface with ethanol to obtain a component to be covered.
[0044] Step S2: Add the raw materials of the cladding material into a high-speed mixer and mix them at a high speed of 1000 rpm for 10 minutes. Then, spread them evenly on the surface of the to-be-clad part through a distributor. The spreading thickness of the cladding material is controlled to be 0.25 mm. Laser cladding is performed under argon protection. The laser power of the laser cladding is 1.5 kW and the laser scanning rate is 300 mm / min. After cladding, the material is air-cooled to room temperature and the cladding surface is machined to achieve the designed size to obtain a high red hardness alloy material.
[0045] Example 3, preparation of high red hardness alloy material, the specific implementation process is as follows:
[0046] (1) Preparation of N-tungsten carbide tantalum powder
[0047] Step A1: Take diethylenetriamine, sodium hydroxide and anhydrous acetone and mix them, pass dry nitrogen for protection, control the temperature at 5°C in an ice-water bath, apply stirring at 180rpm, slowly add cyanuric chloride to react for 1.8h, then raise the temperature to 50°C and continue the reaction for 2.6h, wherein the amount ratio of cyanuric chloride, diethylenetriamine, sodium hydroxide and anhydrous acetone is 0.1mol:0.16mol:0.6g:90mL. After the reaction is completed, filter to remove sodium hydroxide, and remove acetone by rotary evaporation to obtain a template.
[0048] Step A2: pre-mix the template agent and dimethylacetamide aqueous solution, then add tungsten hexachloride and tantalum ethoxide and mix well, increase the pressure to 3 bar, raise the temperature to 110°C, slowly inject ammonia water, and reflux for 4.5 hours, wherein the dosage ratio of tungsten hexachloride, tantalum ethoxide, template agent, ammonia water and dimethylacetamide aqueous solution is 1g:0.15g:0.9g:7mL:35mL, the volume fraction of dimethylacetamide aqueous solution is 60%, and the ammonia water adopts an industrial raw material with a mass fraction of 20%. After the reaction is completed, centrifuge to take the bottom precipitate, wash and dry to obtain a precursor.
[0049] Step A3: Place the precursor in a plasma sintering furnace, first perform carbonization roasting at 580°C for 1.4h, then continue to heat up to 1480°C for nitridation sintering for 18min, cool to 500°C, air-cool, grind and disperse to obtain N-tungsten carbide tantalum powder.
[0050] (2) Preparation of high red hardness alloy materials
[0051] Preparation of cladding material: take raw materials according to weight percentage, 55wt% of N-tungsten carbide tantalum micropowder, which is self-made in this embodiment; 7.5wt% of chromium carbide powder, which is selected from FCr3C2-1 type raw material of Zhuzhou Guangyuan Hard Materials Co., Ltd.; 3.5wt% of nickel powder, which is selected from MDNi-A1 type raw material of Jiangsu Mengda New Materials Technology Co., Ltd.; 34wt% of atomized iron powder, which is selected from HT40.37 type raw material of Hangzhou Yitong New Materials Co., Ltd.
[0052] Step S1: Take the cut M2 high-speed steel substrate, polish the surface with 150-grit sandpaper, and then clean and dry the polished surface with ethanol to obtain a component to be covered.
[0053] Step S2: Add the raw materials of the cladding material into a high-speed mixer and mix them at a high speed of 1000 rpm for 10 minutes. Then, spread them evenly on the surface of the to-be-clad part through a distributor. The spreading thickness of the cladding material is controlled to be 0.25 mm. Laser cladding is performed under argon protection. The laser power of the laser cladding is 1.6 kW, and the laser scanning rate is 280 mm / min. After cladding, the material is air-cooled to room temperature, and the cladding surface is machined to achieve the designed size to obtain a high red hardness alloy material.
[0054] Example 4, preparation of high red hardness alloy material, the specific implementation process is as follows:
[0055] (1) Preparation of N-tungsten carbide tantalum powder
[0056] Step A1: Take diethylenetriamine, sodium hydroxide and anhydrous acetone and mix them, pass dry nitrogen for protection, control the temperature at 0°C in an ice-water bath, apply stirring at 240rpm, slowly add cyanuric chloride to react for 1.9h, then raise the temperature to 50°C and continue the reaction for 3h, wherein the amount ratio of cyanuric chloride, diethylenetriamine, sodium hydroxide and anhydrous acetone is 0.1mol:0.16mol:0.6g:100mL. After the reaction is completed, filter to remove sodium hydroxide, and remove acetone by rotary evaporation to obtain a template.
[0057] Step A2: pre-mix the template agent and dimethylacetamide aqueous solution, then add tungsten hexachloride and tantalum ethoxide and mix well, increase the pressure to 3.5 bar, raise the temperature to 105°C, slowly inject ammonia water, and reflux for 4.8 hours, wherein the dosage ratio of tungsten hexachloride, tantalum ethoxide, template agent, ammonia water and dimethylacetamide aqueous solution is 1g:0.17g:0.9g:6mL:35mL, the volume fraction of dimethylacetamide aqueous solution is 60%, and the ammonia water adopts an industrial raw material with a mass fraction of 20%. After the reaction is completed, centrifuge to take the bottom precipitate, wash and dry to obtain a precursor.
[0058] Step A3: Place the precursor in a plasma sintering furnace, first perform carbonization roasting at 600°C for 1.5 hours, then continue to heat up to 1500°C for nitridation sintering for 16 minutes, cool to 500°C, take out of the furnace and air cool, grind and disperse, and obtain N-tungsten carbide tantalum powder.
[0059] (2) Preparation of high red hardness alloy materials
[0060] Preparation of cladding material: take raw materials according to weight percentage, 55wt% of N-tungsten carbide tantalum micropowder, which is self-made in this embodiment; 8wt% of chromium carbide powder, which is selected from FCr3C2-1 type raw material of Zhuzhou Guangyuan Hard Materials Co., Ltd.; 4.2wt% of nickel powder, which is selected from MDNi-A1 type raw material of Jiangsu Mengda New Materials Technology Co., Ltd.; 32.8wt% of atomized iron powder, which is selected from HT40.37 type raw material of Hangzhou Yitong New Materials Co., Ltd.
[0061] Step S1: Take the cut M2 high-speed steel substrate, polish the surface with 150-grit sandpaper, and then clean and dry the polished surface with ethanol to obtain a component to be covered.
[0062] Step S2: Add the raw materials of the cladding material into a high-speed mixer and mix them at a high speed of 1000 rpm for 10 minutes. Then, spread them evenly on the surface of the to-be-clad part through a distributor. The spreading thickness of the cladding material is controlled to be 0.25 mm. Laser cladding is performed under argon protection. The laser power of the laser cladding is 1.7 kW, and the laser scanning rate is 260 mm / min. After cladding, the material is air-cooled to room temperature, and the cladding surface is machined to achieve the designed size to obtain a high red hardness alloy material.
[0063] Comparative Example 1
[0064] This comparative example refers to Example 4, and directly performs laser heat treatment on the surface of the component to be coated.
[0065] Comparative Example 2
[0066] This comparative example refers to Example 4, except that the N-tungsten carbide tantalum powder is replaced with tungsten carbide powder of the same weight percentage, and the FWC-1 raw material is selected from Zhuzhou Sanli Cemented Carbide New Materials Co., Ltd. The laser cladding power is adjusted to 1.9 kW, the laser scanning rate is 200 mm / min, and the rest of the implementation process is exactly the same.
[0067] The alloy material prepared as above was kept at 600°C for 4 hours and then air-cooled to room temperature, and the surface Rockwell hardness was tested;
[0068] The alloy material prepared as above was heated to 500°C by an induction coil, cooled to room temperature by water spraying, and cycled for 100 cycles. The crack state on the alloy surface was detected by an ultrasonic flaw detector, including the number of cracks La (crack length not less than 10 μm), the maximum crack length Lmax, and the maximum crack depth Hmax. The specific test data are shown in Table 1:
[0069] Table 1
[0070]
[0071] It can be seen from the test results in Table 1 that the cladding layer of the embodiment significantly improves the red hardness of the M2 high-speed steel substrate, and the surface red hardness is comparable to that of M42 high-speed steel. The cladding layer has better thermal fatigue resistance stability than the existing tungsten carbide-based cladding layer.
[0072] like Figure 1 , is a scanning electron microscope image of the N-tungsten carbide tantalum micropowder in Example 4. It can be seen that the N-tungsten carbide tantalum micropowder is an irregular dense particle with a submicron size.
[0073] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0074] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A high red hardness alloy material, consisting of an M2 high speed steel substrate and a cladding layer, characterized in that: The cladding material of the cladding layer is composed of the following components: 52-58wt% N-tungsten carbide tantalum powder, 6.5-9wt% chromium carbide powder and 3.2-4.4wt% nickel powder, and the balance is atomized iron powder; The N-tungsten carbide tantalum powder is prepared by the following method: Step A1: Diethylenetriamine, sodium hydroxide and anhydrous acetone are mixed, dry nitrogen is introduced for protection, the temperature is controlled at 0-10°C in an ice-water bath, cyanuric chloride is slowly added with stirring for 1.5-2h, and then the temperature is raised to 45-55°C and the reaction is continued for 2-3h. After the reaction is completed, the mixture is filtered and rotary evaporated to obtain a template; Step A2: premix the template and dimethylacetamide aqueous solution, then add tungsten hexachloride and tantalum ethoxide and mix well, increase the pressure to 2.5-3.5 bar, raise the temperature to 100-115°C, slowly inject ammonia water, reflux for 4-5 hours, centrifuge after the reaction, take the bottom precipitate, wash and dry to obtain a precursor; Step A3: Place the precursor in a plasma sintering furnace, perform carbonization roasting and nitridation sintering in sequence, then cool to 500°C in the furnace, air-cool out of the furnace, grind and disperse, and obtain N-tungsten carbide tantalum powder.
2. A high red hardness alloy material according to claim 1, characterized in that: The dosage ratio of cyanuric chloride, diethylenetriamine, sodium hydroxide and anhydrous acetone is 0.1 mol: 0.16-0.17 mol: 0.5-0.7 g: 85-100 mL.
3. A high red hardness alloy material according to claim 2, characterized in that: The dosage ratio of tungsten hexachloride, tantalum ethoxide, template, ammonia water and dimethylacetamide aqueous solution is 1g: 0.14-0.18g: 0.8-1g: 5-8mL: 30-40mL.
4. The high red hardness alloy material according to claim 1, characterized in that: The temperature of carbonization roasting is 550-620°C, and the roasting time is 1.2-1.6h.
5. The high red hardness alloy material according to claim 1, characterized in that: The temperature of nitriding sintering is 1450-1520°C, and the sintering time is 15-20min.
6. The method for preparing a high red hardness alloy material according to any one of claims 1 to 5, characterized in that: The steps include: Step S1: grinding the surface of the M2 high-speed steel substrate, cleaning the ground surface with ethanol, and drying to obtain a component to be coated; Step S2: Mix the raw materials of the cladding material and spread them on the surface of the part to be clad, perform laser cladding under the protection of argon gas, and machine the cladding surface after cooling to obtain a high red hardness alloy material.
7. The method for preparing a high red hardness alloy material according to claim 6, characterized in that: The spreading thickness of the cladding material is 0.25-0.3mm.
8. The method for preparing a high red hardness alloy material according to claim 7, characterized in that: The laser power of laser cladding is 1.5-1.7kW, and the laser scanning rate is 250-300mm / min.
Citation Information
Patent Citations
Fixed-cutter matrix bits with repairable gauge pads
CN109891045A
Hard alloy and W-based complex carbide powder used as raw material
CN1497053A